Photoswitchable Serotonins for Optical Control of the 5‐HT2A Receptor. Issue 18 (7th March 2022) - Morstein, Johannes; Romano, Giovanna; Hetzler, Belinda E.; Plante, Ambrose; Haake, Caleb; Levitz, Joshua; Trauner, Dirk
Abstract: Serotonin receptors play central roles in neuromodulation and are critical drug targets for psychiatric disorders. Optical control of serotonin receptor subtypes has the potential to greatly enhance our understanding of the spatiotemporal dynamics of receptor function. While other neuromodulatory receptors have been successfully rendered photoswitchable, reversible photocontrol of serotonin receptors has not been achieved, representing a major gap in GPCR photopharmacology. Herein, we develop the first tools that allow for such control. Azo5HT‐2 shows light‐dependent 5‐HT2A R agonism, with greater activity in the cis ‐form. Based on docking and test compound analysis, we also develop photoswitchable orthogonal, remotely‐tethered ligands (PORTLs). These BG‐Azo5HT s provide rapid, reversible, and repeatable optical control following conjugation to SNAP‐tagged 5‐HT2A R. Overall, this study provides a foundation for the broad extension of photopharmacology to the serotonin receptor family. Abstract : The first‐in‐class photoswitchable agonists for the 5HT2A receptor (serotonin family GPCR) have been developed. Bifunctional, tethered variants (PORTLs) enable genetically targeted optical control.